2014
DOI: 10.1371/journal.pone.0099702
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Signals via PAR2 and Generates a Novel Tethered Ligand Receptor Agonist

Abstract: Protease-activated receptor-2 is widely expressed in mammalian epithelial, immune and neural tissues. Cleavage of PAR2 by serine proteases leads to self-activation of the receptor by the tethered ligand SLIGRL. The contribution of other classes of proteases to PAR activation has not been studied in detail. Cathepsin S is a widely expressed cysteine protease that is upregulated in inflammatory conditions. It has been suggested that cathepsin S activates PAR2. However, cathepsin S activation of PAR2 has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 37 publications
(39 reference statements)
1
50
1
1
Order By: Relevance
“…to reveals a the tethered ligand 42 KVDGTS, which, like the trypsin-exposed AP SLIGRL, stimulates Ca 2ϩ signaling in HeLa cells, albeit with reduced potency (58). However, we found no evidence that Cat-S induced mobilization of intracellular Ca 2ϩ in KNRK or HEK cells expressing PAR 2 , but instead observed that Cat-S stimulates a TRPV4-dependent influx of extracellular Ca 2ϩ ions in nociceptive neurons.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…to reveals a the tethered ligand 42 KVDGTS, which, like the trypsin-exposed AP SLIGRL, stimulates Ca 2ϩ signaling in HeLa cells, albeit with reduced potency (58). However, we found no evidence that Cat-S induced mobilization of intracellular Ca 2ϩ in KNRK or HEK cells expressing PAR 2 , but instead observed that Cat-S stimulates a TRPV4-dependent influx of extracellular Ca 2ϩ ions in nociceptive neurons.…”
contrasting
confidence: 64%
“…Thus, the selectivity with which Cat-S cleaves PAR 2 probably relies on a series of mutual interactions from numerous sites, which requires future study. In addition to the E 56 2T 57 site, Cat-S can also cleave PAR 2 more proximally at G 41 2K 42 (58). However, this study did not assess whether Cat-S cleaves PAR 2 at the site that we have identified.…”
mentioning
confidence: 81%
“…9,31,32 Cat-S consistently induced ED in vitro and in vivo through PAR2, which is in line with a recent report on Cat-S cleavage of the extracellular domain of PAR2 required for activation. 16 Madhusudhan et al 33 reported human kidney to stain positive for PAR2 in podocytes. We got similar results with several different antibodies in mouse kidney, but PAR2-deficient kidney sections unraveled this staining as unspecific (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…15 So far, the functional role of Cat-S has been related to its elastolytic protease activity in macrovascular diseases, [7][8][9][10][11] but Cat-S was also recognized as a protease-activated receptor-2 (PAR2) agonist. 16 Hence, we speculated on functional roles of Cat-S also on microvascular disease. Our data confirm this hypothesis and identify Cat-S as a circulating trigger of ED by activating PAR2 on endothelial cells, a process promoting microvascular complications in diabetes (e.g., DN and diabetic retinopathy [DR]).…”
mentioning
confidence: 99%
“…biased agonism). Such proteases include cathepsin S, which cleaves at Gly 41 2Lys 42 (30) (32). However, the precise molecular mechanisms and the physiological consequences of biased protease signaling are poorly defined.…”
mentioning
confidence: 99%